Hubungan antara Beberapa Sifat Fisika Tanah Inceptisol Pasca Penambangan Tanah - Efriandi, Efriandi; Nurwahyudi, M Agust; Ariadi, Zepri; Karenina, Tili; Tania Defriyanti, Wenni (Seminar Nasional Lahan Suboptimal, 2022)
Efriandi E, Nurwahyudi MA, Ariadi Z, Karenina T, Defriyanti WT.  2022. Relationship between some physical properties of soil inceptisol post soil mining. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 1067-1072.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Research to know and observes change of morphology after done soil mining for brick industry. The purpose of this study is to find out and observe changes in the physical properties of the soil after taah mining for the brick industry.Research is done by observing 4 soil profile that is (1) soil that is not is mined (control); (2) soil which have been mined and leaved more than 10 years; (3) soil which have been mined and leaved ± 5 year; (4) soil which have been mined and leaved between 1-3 years. Inceptisol soil has limited physical properties for the development of the root system and soil roots, has a thin effective depth for tillage, has a larger density due to some of the pores filled with dust particles. Based on the distribution of each soil order on the earth's surface, inceptisols have an area of about 15% of the earth's surface area. Classified as fertile land for agricultural land. Result of research indicates that Inceptisol experience change of morphology soil colour, structure, consistency, root, horizon boundary. Inceptisol which has been mined for brick base material experiences change of morphology and soil physical properties. The need of doing of research that is further about land rehabilitation technique so that serve the purpose of consideration in doing repair of area ex-mined.